Deliberate poisoning with dinitrophenol (DNP): an unlicensed weight loss pill. Issue 2 (15th February 2010) - Bartlett, James; Brunner, Michael; Gough, Katie
Abstract : A 46-year-old man took a lethal dose of an agent called dinitrophenol (DNP). He presented 11 h after ingestion with loin pain, diarrhoea and vomiting. He rapidly deteriorated with profound hyperthermia, acute renal failure, hyperkalaemia, metabolic acidosis and eventually haemodynamic instability. Despite aggressive supportive measures and rapid sequence induction, he deteriorated and died 21 h after ingestion. DNP is a metabolic poison that acts by uncoupling oxidative phosphorylation, leading to uncontrolled hyperthermia. It is an illegal weight loss agent that is used by body builders and is freely available on many internet websites. This case highlights the potential for patients to obtain and ingest exotic poisons. A summary of currently recommended treatment and a review of the literature on DNP is included, as well as a discussion of therapies that may be effective in treating hyperthermia in this situation.